Analysis of Factors Affecting the Income of Recent Migrant Workers in Denpasar City - Aluna Giacinta Lestari; Ida Ayu Gde Dyastari Saskara (CV. Lenggogeni Data Publishing, 2025)
This study aims to analyze the influence of education level, work experience, type of occupation, and number of dependents on the income of recent migrant workers in Denpasar City, both simultaneously and partially. The research applies a quantitative approach using data analysis to examine the relationships among variables. The results show that education level, work experience, type of occupation, and number of dependents simultaneously have a significant effect on migrant workers’ income. Partially, education level has a negative and significant effect on income, while work experience and number of dependents have a positive and significant effect. Employment in the formal sector tends to provide higher income compared to the informal sector. These findings indicate a mismatch between formal education and labor market demands, as well as the importance of work experience in increasing income. This study is expected to serve as a reference for policymakers in formulating strategies to improve human resource quality and the welfare of migrant workers in Denpasar City.